Perceived instructional leadership roles of principals of secondary schools in Sarawak, Malaysia - Rijeng, Anak Jahet. (1998)
This study was carried out in order to determine perception of principals of secondary schools in Sarawak regarding their instructional leadership roles and factors associated with those roles. The population of the study is all the one hundred and forty principals of secondary school in Sarawak. A total of ninety-seven principals were selected as the sample for the study. This represents 66.4 percent of all the principals in Sarawak. Vocational school principals were excluded from the study. The questionnaire used in this study is an adaptation of the Principal Instructional Management Rating Scale (PIMRS) developed by Hallinger and Murpy in 1985. The adapted version used in this study reclassifies the instructional leadership roles of principals into five categories based on those listed by Krug (1992).